2014
DOI: 10.3892/mmr.2014.2116
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-133b downregulation and inhibition of cell proliferation, migration and invasion by targeting matrix metallopeptidase-9 in renal cell carcinoma

Abstract: microRNA (miRNA)-133b has been revealed to be downregulated in head and neck/oral, bladder, human non-small cell lung, colorectal and esophageal squamous cell cancer. The present study examined the expression of miR-133b in renal cell carcinoma (RCC) cell lines and the effects of miRNA-133b on RCC cell proliferation, migration and invasion. Quantitative polymerase chain reaction was used to detect the expression of miR-133b in RCC cell lines. Following transfection of miR-133b, the expression of miR-133b was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…Downregulation of miR‐133b had also been observed in other cancers, including colorectal cancer, gastric cancer, and renal cell carcinoma 19, 20, 21. Furthermore, we found downregulation of miR‐133b associates with aggressive clinicopathological features of UCB.…”
Section: Discussionsupporting
confidence: 68%
“…Downregulation of miR‐133b had also been observed in other cancers, including colorectal cancer, gastric cancer, and renal cell carcinoma 19, 20, 21. Furthermore, we found downregulation of miR‐133b associates with aggressive clinicopathological features of UCB.…”
Section: Discussionsupporting
confidence: 68%
“…miR-133b was reported as a kidney tumor suppressor [23] and was dysregulated in polycystic kidney disease [24]. Wang groups found that the miR-133b-3p which was downregulated in bone marrow mesenchymal stem cell-derived microvesicles of older rats, remarkably inhibited TGF-b1-mediated EMT in HK2 cells, suggesting that these may play a role in the fibrosis of aging renal tissues [25].…”
Section: Discussionmentioning
confidence: 99%
“…Zhao and colleagues reported that miR-133b was downregulated in osteosarcoma tissues, inhibited proliferation, migration and invasion, and promoted apoptosis of osteosarcoma cells [22]. Moreover, Wu et al showed that miR-133b was downregulated in renal cell carcinoma, and suppressed the cell proliferation, migration and invasion by targeting MMP9 [23]. …”
Section: Discussionmentioning
confidence: 99%